2013
DOI: 10.1007/s00216-013-6977-z
|View full text |Cite
|
Sign up to set email alerts
|

In situ NMR spectroelectrochemistry for the structure elucidation of unstable intermediate metabolites

Abstract: In situ NMR spectroelectrochemistry is presented in this study as a useful hybrid technique for the chemical structure elucidation of unstable intermediate species. An experimental setting was designed to follow the reaction in real time during the experimental electrochemical process. The analysis of (1)H NMR spectra recorded in situ permitted us (1) to elucidate the reaction pathway of the electrochemical oxidation of phenacetin and (2) to reveal the quinone imine as a reactive intermediate species without u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 25 publications
2
57
0
1
Order By: Relevance
“…Other studies have described the formation of NAPQI after paracetamol (dehydrogenation) or phenacetin (aromatic ether dealkylation) oxidation and confirmed the quick, efficient trapping by GSH [14,30]. Moreover, electrochemical oxidation of phenacetin combined with pyridinium chemical trapping demonstrated the formation of an oxonium intermediate involved in the electrochemical mechanistic pathway (Fig.…”
Section: Electrophilic Aryl Reactive Metabolitesmentioning
confidence: 80%
See 1 more Smart Citation
“…Other studies have described the formation of NAPQI after paracetamol (dehydrogenation) or phenacetin (aromatic ether dealkylation) oxidation and confirmed the quick, efficient trapping by GSH [14,30]. Moreover, electrochemical oxidation of phenacetin combined with pyridinium chemical trapping demonstrated the formation of an oxonium intermediate involved in the electrochemical mechanistic pathway (Fig.…”
Section: Electrophilic Aryl Reactive Metabolitesmentioning
confidence: 80%
“…2) [20,22,30] and acebutolol [9,31,32] were chosen as models of aromatic ether O-dealkylation. Lohmann et al reported the comparison between electrochemical oxidation and rat-liver microsome incubations for three active pharmaceutical ingredients [15].…”
Section: Electrophilic Aryl Reactive Metabolitesmentioning
confidence: 99%
“…Active transport necessitates the solution to be continuously introduced and removed to and from the probe/vial [19]. Passive transport by diffusion is slow, difficult to control and high conversion rates are hard to achieve [16,21]. This is true for both in-probe and in-situ set-ups [8].…”
Section: In-probe Ec-nmrmentioning
confidence: 96%
“…WE, CE and RE are labelled and the NMR sensitive volume is marked instead of the position of the RF coils. {Adapted from [16] with kind permission from Springer Science and Business Media}.…”
Section: In-situ Ec-nmrmentioning
confidence: 99%
“…More recently, Bussy et al [17] introduced a simplified spectroelectrochemical cell, based on carbon microfiber electrode proposed by Klod et al [16]. Carbon microfibers are inserted into a glass capillary tube.…”
Section: In Situ Nmr Spectroelectrochemistrymentioning
confidence: 99%